Global Research Trends in Animal Feed Nutrition and Industry Development: a Bibliometric Analysis - Nurrofingah, Ulfa; Widjaya, Fensa Eka (Journal of Engineering Science and Technology Management, 2025)
The feed industry is a cornerstone of global livestock production and food security, with feed costs representing more than half of total production expenses. In response to rising demand for animal protein and growing sustainability concerns, research in animal feed nutrition has advanced rapidly. This study maps global research trends in feed nutrition and industry development through a bibliometric analysis of 747 publications retrieved from Scopus (2000–2025). Data were analyzed using the Bibliometrix R-package via Biblioshiny. Results show a marked increase in publications, particularly in the past decade. Core journals identified include Poultry Science, Animals, and Aquaculture, serving as key platforms for knowledge dissemination. Productive authors are largely from Asia, with China leading, while major institutions include China Agricultural University, Universiti Putra Malaysia, IPB University, and Universitas Brawijaya. Highly cited works address poultry nutrition, feed additives, and sustainable production. Collaboration networks reveal strong partnerships between China, the United States, and Europe. Trending topics indicate a shift from traditional themes (e.g., diet supplementation, phosphorus, physiology) to emerging areas such as sustainability, aquaculture, immunity, and animal models. Overall, findings highlight a paradigm shift in feed research toward integrated approaches that balance productivity, health, resource efficiency, and environmental impact, offering strategic insights for academia, industry, and policymakers.